2020
DOI: 10.21203/rs.3.rs-28838/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Promoter methylation, transcription, and retrotransposition of LINE-1 in colorectal adenomas and adenocarcinomas

Abstract: Background: LINE-1, Alu, and SVA elements are non-LTR retrotransposons that create approximately one-third of the human genome. The loss of tight control mechanisms on the function of mobile elements has been implicated in many human diseases. The methylation of the CpG islands of the LINE-1 promoter is one of these mechanisms. In this study, we determined the promoter methylation and the expression of LINE-1 in three stages of colorectal non-advanced adenoma, advanced adenoma, and adenocarcinoma. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Rather than the CNA or mutation burden, the SV landscape best describes the genomic variability across the cohort and, in keeping with this, there is an increasing number and complexity of rearrangements and LINE-1 retrotransposon events with advancing grade. Whilst these complex, large-scale rearrangements and retrotransposons are increasingly understood to have roles in multiple cancers, it has not been appreciated to this extent in pre-malignant disease, although LINE-1 retrotransposon activity has been demonstrated previously in very small numbers of pre-cancers, namely including benign BE 54 and colorectal adenomas 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Rather than the CNA or mutation burden, the SV landscape best describes the genomic variability across the cohort and, in keeping with this, there is an increasing number and complexity of rearrangements and LINE-1 retrotransposon events with advancing grade. Whilst these complex, large-scale rearrangements and retrotransposons are increasingly understood to have roles in multiple cancers, it has not been appreciated to this extent in pre-malignant disease, although LINE-1 retrotransposon activity has been demonstrated previously in very small numbers of pre-cancers, namely including benign BE 54 and colorectal adenomas 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…LINEs are retrotransposable elements identified in numerous eukaryotic genomes. These are highly methylated in normal somatic cells and, therefore, are mostly inhibited, thus preventing their potential to cause genomic instability (78). Full-length LINE-1 can lead to adenoma formation and cancer progression, and the activity of LINE-1 is dependent on the epigenetic regulation of its promoter (79).…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
“…Jiang et al (81) examined promoter methylation of LINE-1 in adenomas and sessile serrated lesions (SSLS); the results showed that high-grade dysplasia (HGD) and increasing size of adenoma were associated with decreased LINE-1 methylation. Shademan et al (78) quantified promoter methylation and LINE-1 transcripts in three stages of CRC, non-advanced adenoma, advanced adenoma and adenocarcinoma. Their results demonstrated that the methylation of the LINE-1 promoter in non-advanced adenoma was significantly higher compared with that in advanced adenoma and adenocarcinoma.…”
Section: Prognostic Biomarkersmentioning
confidence: 99%